2010
DOI: 10.1177/0258042x1003500207
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Intrapreneurship Relationship: Reward as a Moderator

Abstract: Purpose: Intrapreneurship refers to employee initiatives in organizations to undertake something new, without being asked to do so. In recent years, enterprises have established “innovation units” to stimulate new ideas and utilize the energy and ideas of the individuals in international enterprises. It involves the process where an individual or a group of individuals, within an established company innovate or create a new organization as sub unit and get involved in the process of wealth creation. The system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, this is not the case; these characteristics of the situation prompt some statue's characteristics, and these characteristics are primarily based on the structure of a role and resources existent in an organization (Badura et al, 2018;Mannix and Sauer, 2006). There are many positive relations between the culture, environment, organization and intrapreneurship, and some researchers found organizational culture crucial for intrapreneurship (Benitez-Amado et al, 2010;Srivastava and Srivastava, 2010). Intrapreneurship can be a role that allows employees to be innovative without neglecting the roles already exists.…”
Section: Results Discussion and Limitationsmentioning
confidence: 99%
“…However, this is not the case; these characteristics of the situation prompt some statue's characteristics, and these characteristics are primarily based on the structure of a role and resources existent in an organization (Badura et al, 2018;Mannix and Sauer, 2006). There are many positive relations between the culture, environment, organization and intrapreneurship, and some researchers found organizational culture crucial for intrapreneurship (Benitez-Amado et al, 2010;Srivastava and Srivastava, 2010). Intrapreneurship can be a role that allows employees to be innovative without neglecting the roles already exists.…”
Section: Results Discussion and Limitationsmentioning
confidence: 99%
“…However, this is not the case. Because there are many posi� ve rela� ons between the culture, environment, organiza� on, and intrapreneurship, some researchers found organiza� onal culture crucial for intrapreneurship (Benitez-Amado et al, 2010;Srivastava & Srivastava, 2010). The more solid-state of culture, Hisrich (1990) defi ned the useful organiza� onal climate characteris� cs, and he found that not forced, but volunteer intrapreneurship, and wholeheartedly support by top management as the most cri� cal aspects.…”
Section: Resultsmentioning
confidence: 99%
“…Kuratko, Ireland, Covin and Hornsby (2005) define CE as the process within an established company whereby an individual, or a group of individuals create a new business, or instigate a renewal or an innovation within the current business. Under this definition, strategic renewal (organisational renewal involving major strategic and/or structural changes), innovation (introducing something new to the market place), and corporate venturing (corporate entrepreneurial efforts that lead to creation of new business organisations within the corporate organisation) are all important and legitimate parts of the corporate entrepreneurial process (Srivastava, Srivastava & Jain, 2011).…”
Section: Corporate Entrepreneurshipmentioning
confidence: 99%